Single cell-produced and in vitro-assembled anti-FcRH5/CD3 T-cell dependent bispecific antibodies have similar in vitro and in vivo properties. Issue 2 (17th February 2019) - Ovacik, Ayse Meric; Li, Ji; Lemper, Marie; Danilenko, Dimitry; Stagg, Nicola; Mathieu, Mary; Ellerman, Diego; Gupta, Vinita; Kalia, Navdeep; Nguy, Trung; Plaks, Vicki; David Johnson, Clarissa; et al.
ABSTRACT: Bispecific antibody production using single host cells has been a new advancement in the antibody engineering field. We previously showed comparable in vitro biological activity and in vivo mouse pharmacokinetics (PK) for two novel single cell variants (v10 and v11) and one traditional dual cell in vitro -assembled anti-human epidermal growth factor receptor 2/CD3 T-cell dependent bispecific (TDB) antibodies. Here, we extended our previous work to assess single cell-produced bispecific variants of a novel TDB against FcRH5, a B-cell lineage marker expressed on multiple myeloma (MM) tumor cells. An in vitro -assembled anti- FcRH5/CD3 TDB antibody was previously developed as a potential treatment option for MM. Two bispecific antibody variants (designs v10 and v11) for manufacturing anti-FcRH5/CD3 TDB in single cells were compared to in vitro- assembled TDB in a dual-cell process to understand whether differences in antibody design and production led to any major differences in their in vitro biological activity, in vivo mouse PK, and PK/pharmacodynamics (PD) or immunogenicity in cynomolgus monkeys (cynos). The binding, in vitro potencies, in vitro pharmacological activities and in vivo PK in mice and cynos of these single cell TDBs were comparable to those of the in vitro -assembled TDB. In addition, the single cell and in vitro -assembled TDBs exhibited robust PD activity and comparable immunogenicity in cynos. Overall, these studies demonstrate that single cell-produced and in vitro -assembled anti-FcRH5/CD3 T-cell dependent bispecific antibodies have similar in vitro and in vivo properties, and support further development of single-cell production method for anti-FcRH5/CD3 TDBs and other single-cell bispecifics.